Addressing Suicide Risk in Patients Living With Dementia During the COVID-19 Pandemic and Beyond. (2nd April 2022) - Portacolone, Elena; Byers, Amy L; Halpern, Jodi; Barnes, Deborah E
Abstract: Alzheimer's disease and related dementias (ADRD) are progressive illnesses characterized by decline in cognitive function that impairs performing daily activities. People with ADRD are at an increased risk of suicide, especially those who have comorbid mental health conditions, have specific types of ADRD, or have been recently diagnosed. The coronavirus disease 2019 (COVID-19) pandemic has increased the distress of people with ADRD, a population also at increased risk of contracting the COVID-19 virus. In this article, we draw on a case study and use the Interpersonal Theory of Suicide to help describe the association between ADRD and suicide risk. Secondly, we call for new strategies to mitigate suicide risk in people living with ADRD during and beyond the current pandemic by using lessons learned from cancer care. Our goal is not to dictate solutions but rather to start the conversation by outlining a framework for future research aimed at preventing death by suicide in people with ADRD. Specifically, we draw on the updated Framework for Developing and Evaluating Complex Interventions to reflect on the complexity of the issue and to break it down into achievable parts to reduce the risk of suicidal behavior (ideation, plans, attempts) in those living with ADRD.